HOLTON, KAN. REV. ORDINANCES No. 169, § 20 at 130, 134-35 (1905) (effective Aug. 8, 1888). - (:unkn) unknown (General Publisher, 1888)
Any preson who shall sell, trade, give, loan or otherwise furnish any pistol, revolver, or toy pistol, by which cartridges or caps may be exploded, or any dirk, bowie knife, brass knuckles, slung shot or any other dangerous weapon to any minor or to any person of notoriously unsound mind, shall, upon conviction, be fined not less than five or more than one hundred dollars.
--
Keywords: TRANSFER - MINORS